Matriarchal Beads: The Resistance, Resurgence, and Reclamation of Traditional Indigenous Beadwork - Wolfe, Tammy (Matrix, 2026)
Beading, weaving, and sewing are Indigenous cultural traditions that have been practiced by many nations across the North American continent since time immemorial; ultimately, these practices carry significant Indigenous knowledges and belief systems. The impact of colonization on Indigenous women throughout the continent limited and reduced the function of their matriarchal roles within their communities. In turn, they have adapted, evolved, and gained a stronger sense of culture and identity through their traditional artistic practices of beadwork; this includes the transmission of knowledge, culture, and identity. Indigenous matriarchs have used the reclamation and resurgence of the traditional practices of beadwork as a form of resistance and decolonization. This article looks to explore, understand, and interpret these issues from the position of a First Nation Ininiw Iskwew (Swampy Cree woman) lens, as the author is a proud matriarch originating from the community of Norway House Cree Nation.